Advances in conceptual modeling : ER 2015 workshops AHA, CMS, EMoV, MoBID, MORE-BI, MReBA, QMMQ, and SCME, Stockholm, Sweden, October 19-22, 2015 : proceedings /: ER 2015 workshops AHA, CMS, EMoV, MoBID, MORE-BI, MReBA, QMMQ, and SCME, Stockholm, Sweden, October 19-22, 2015 : proceedings. (2015) - Unknown
No abstract available